Sosialisasi dan Pelatihan Pemasaran Digital serta Edukasi Legalitas Usaha untuk Meningkatkan Daya Saing UMKM di Desa Karangsari - Erin Soleha; Ahmad Rasyiddin; Rama Wijaya; Zahra Nayla Darmawan; Nabil Hawari; Nur Fatimah (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2024)
Business legality is a crucial element in the development of Micro, Small and Medium Enterprises (MSMEs) in Indonesia. Karangsari Village, as one of the MSME centers, is facing challenges in adopting Business Identification Numbers (NIB) and implementing digital marketing. This research aims to identify the impact of implementing NIB on MSMEs in Karangsari Village and explore the obstacles and opportunities in its implementation. The methods used are case studies and field surveys. The research results show that although NIB can improve legality and market access, low digital literacy is a major obstacle. It is hoped that the socialization and training carried out in Karangsari Village can increase understanding and adoption of NIB and digital marketing by MSMEs, so as to strengthen their competitiveness in the market.